INOVASI PENDIDIKAN MADRASAH (INNOVATION IN MADRASAH EDUCATION) - Arfiana Sihombing; Budiman Budiman (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2025)
The purpose of this study is to be able to analyze madrasah education innovation. The type of research used is qualitative with a literature study approach. The data collection process in this study was carried out by collecting books, journals, and similar research, related to the title of the researcher's research, in order to obtain clear and accurate information. Then concluded based on descriptive text. Based on the results of the study, it was found that madrasahs before independence to madrasahs stated in Law No. 20 of 2003 have always experienced innovation, including superior labels and models, in madrasahs that always upgrade their institutions. Madrasah opportunities are very wide open, starting from the use of technology and community expectations for quality education. With challenges in madrasah innovation, namely madrasah infrastructure, human resources, and community expectations. Hopes in madrasah innovation are of course based on integrative education, curriculum development, human resource development, and community empowerment.